Invasive diagnostic techniques in idiopathic interstitial pneumonias. Issue 1 (January 2016) - Poletti, Venerino; Ravaglia, Claudia; Gurioli, Carlo; Piciucchi, Sara; Dubini, Alessandra; Cavazza, Alberto; Chilosi, Marco; Rossi, Andrea; Tomassetti, Sara
Abstract: Fibrosing interstitial lung diseases (f‐ILDs) represent a heterogeneous group of disorders in which the aetiology may be identified or, not infrequently, remain unknown. Establishing a correct diagnosis of a distinct f‐ILD requires a multidisciplinary approach, integrating clinical profile, physiological and laboratory data, radiological appearance and, when appropriate, histological findings. Surgical lung biopsy is still considered the most important diagnostic tool as it is able to provide lung samples large enough for identification of complex patterns such as usual interstitial pneumonitis (UIP) and nonspecific interstitial pneumonitis. However, this procedure is accompanied by significant morbidity and mortality. Bronchoalveolar lavage is still a popular diagnostic tool allowing identification of alternative diagnoses in patients with suspected idiopathic pulmonary fibrosis (IPF) when an increase in lymphocytes is detected. Conventional transbronchial lung biopsy has a very low sensitivity in detecting the UIP pattern and its role in this clinical‐radiological context is marginal. The introduction of less invasive methods such as transbronchial cryobiopsy show great promise to clinical practice as they can be used to obtain samples large enough to morphologically support a diagnosis of IPF or other idiopathic interstitial pneumonias, along with fewer complications. Recent advances in the field suggest that less invasive methods of lung sampling, without significant side effects, in combination with other diagnostic methods could replace the need for surgical lung biopsy in the future. Indeed, these new multidisciplinary procedures may become the main diagnostic work‐up method for patients with suspected idiopathic interstitial pneumonia.